Hsp70 as a Potential Biomarker of Tolerization of Cryopreserved Mononuclear Cells-Derived Dendritic Cells - Goltsev, Anatoliy; Dubrava, Tetyana; Lutsenko, Olena; Gaevska, Yulia; Bondarovych, Mykola; Ostankov, Maksym (Problems of Cryobiology and Cryomedicine, 2025)
The work investigated the effect of three cryopreservation regimens of bone marrow mononuclear cells (MNCs) of CBA/H mice under the protection of a 10% dimethyl sulfoxide solution with a slow cooling rate of 1 deg / min: regimen 1 – to –80ºС; regimen 2 – to –40ºС; regimen 3 – to –25ºС with subsequent immersion of samples into liquid nitrogen (–196ºС) on the expression rate of heat shock protein with a molecular weight of 70 kDa (Hsp70) in MNCs and dendritic cells (DCs) obtained from them in vitro. The DCs tolerogenic potential was assessed after their use in adaptive therapy in mice with adjuvant arthritis by the ability to induce regulatory T cells (Treg) in spleen and minimize the arthritis index, as a clinical index of the pathology development. The dependence of expression rate of the Hsp70 protein in MNCs on the freezing mode was proven, as well as the signifi cance of this protein content in the manifestation of tolerogenic potential of DCs formed from them in vitro. The ability of cryopreservation according to regimen 2 to increase the Hsp70 content in MNCs was shown. The functional potential of DCs grown from cryopreserved MNCs with regimen 2 demonstrated their higher tolerogenic activity compared to DCs derived from native MNCs and cryopreserved with the regimens 1 and 3 MNCs. The maximum content of Hsp70 in DCs when using regimen 2 was consistent with that of Treg formed in animals with adjuvant arthritis after the administration of these cells, as well as it was accompanied by the most pronounced normalization of clinical signs of pathology. The findings demonstrate the ability of cryopreservation to regulate the Hsp70 expression rate as well as tolerogenic potential of DCs formed from cryopreserved precursors, increasing their use effectiveness in adaptive therapy of autoimmune diseases. Probl Cryobiol Cryomed 2024; 34(4):268–281